De ilícito a lícito: o que mudou no mercado após a descriminalização da cannabis na República Oriental do Uruguai (2013-2020)? - (:unkn) unknown (Universidade Federal do Pampa, 2021)
The present final work paper presents the developments of cannabis legalizations in the Oriental Republic of Uruguay and the response of its domestic consumption, placing these elements in the geo-economics context of South America. The central problem of this investigation is to understand the change in the market after the cannabis’ new legislation in Uruguay (2013-2020). Thus, the mobilization for the use of different theories that seek to explain the behavior of the State, such as Securitization and International Regimes as well as the behavior of the Market, with a focus on the social aspect of the Economic Theory, has the necessary framework for this research. The main objective of this work is to carry out a synthetic description on the effects of cannabis regulatory policies and the consequences of these elements years later, thus seeking to cover the main issues addressed in the relevant literature and in the interviews carried out. For this reason, this work uses the case study to relate the legalization of cannabis in Uruguay with the increased demand for products and byproducts related to this plant in the local and international market, based on the dynamics of the emergence of a culture based on the taste of consumers under the influence of social factors - destigmatization of the consumer, search for quality products, state support and international debates on the subject. Based on this framework, a second level of analysis was proposed, now qualitative, which sought to deepen the understanding of the concept of legalization of the substance previously illegal in the context of the market and its demands.
From illicit to licit: what has changed in the market after the decriminalization of cannabis in the Oriental Republic of Uruguay (2013-2020)?
Keywords: Cannabis; Legalização; Uruguai; Segurança Internacional; Desestigmatização; Mercado Legal; Cannabis; Legalization; Uruguay; International Security; Destigmatization; Legal Market; CNPQ::CIENCIAS SOCIAIS APLICADAS